Compounds Antioxide of Extract Yellow and Green Bamboo Shoot - Edy Soesanto (Universitas Muhammadiyah Semarang, 2018)
Bamboo shoot is a plant that is very easy to find in Indonesia and can grow anywhere, bamboo shoot very cheap and has been used by people in the world as food ingredients since time ago. Beside that, bamboo shoot also has a function associated with the nature of hipokolesterolemi, so it can be used as an alternative non-pharmacological treatment or as a traditional medicine derived from medicinal plants (complementary therapies). This research is very determine the levels of phenol, plavonoid, and vitamin E from bamboo shoots yellow and green bamboo. Bamboo bamboo in thinly sliced and dried with 80 ° C oven for 24 hours and mashed to bamboo bamboo shoots and then extraction using 70% ethanol to be analyzed antioxidant content of phenol, plavonoid, and vitamin E by using spectrophotometer. The result of antioxidant compound, antioxidant compound of Vitamin E bamboo green bamboo shoot from yellow bamboo extract is 0,2864%, phenol antioxidant compound in bamboo green bamboo shoot extract bigger than yellow bamboo extract that is 2,3385%, antioxidant compound Plavonoid bamboo green bamboo shoot extract more great when compared with yellow bamboo extract that is equal to 0.02778%. Thus both bamboo shoot extract has a good antioxidant potential and can be used as a traditional medicine antiaterosklerosis derived from medicinal plants (complementary therapies).